Sequential chemoimmunotherapy of fludarabine, mitoxantrone, and cyclophosphamide induction followed by alemtuzumab consolidation is effective in T‐cell prolymphocytic leukemia. Issue 12 (19th March 2013) - Hopfinger, Georg; Busch, Raymonde; Pflug, Natali; Weit, Nicole; Westermann, Anne; Fink, Anna‐Maria; Cramer, Paula; Reinart, Nina; Winkler, Dirk; Fingerle‐Rowson, Günter; Stilgenbauer, Stephan; Döhner, Hartmut; et al.
Abstract : BACKGROUND: Scarce systematic trial data have prevented uniform therapeutic guidelines for T‐cell prolymphocytic leukemia (T‐PLL). A central need in this historically refractory tumor is the controlled evaluation of multiagent chemotherapy and its combination with the currently most active single agent, alemtuzumab. METHODS: This prospective multicenter phase 2 trial assessed response, survival, and toxicity of a novel regimen in previously treated (n = 9) and treatment‐naive (n = 16) patients with T‐PLL. Induction by fludarabine, mitoxantrone, and cyclophosphamide (FMC), for up to 4 cycles, was followed by alemtuzumab (A) consolidation, up to 12 weeks. RESULTS: Of the 25 patients treated with FMC, 21 subsequently received alemtuzumab. Overall response rate to FMC was 68%, comprising 6 complete remissions (all bone‐marrow confirmed) and 11 partial remissions. Alemtuzumab consolidation increased the intent‐to‐treat overall response rate to 92% (12 complete remissions; 11 partial remissions). Median overall survival after FMC‐A was 17.1 months and median progression‐free survival was 11.9 months. Progression‐free survival tended to be shorter for patients with high‐level T‐cell leukemia 1 oncoprotein expression. Hematologic toxicities were the most frequent grade 3/4 side effects under FMC‐A. Exclusively in the 21 alemtuzumab‐consolidated patients, 13 cytomegalovirus reactivations were observed; 9 of these 13 represented a clinically relevant infection. CONCLUSIONS: FMC‐A is a safe and efficient protocol in T‐PLL, which compares favorably to published data. Cancer 2013;119:2258–2267. © 2013 American Cancer Society.